2018
DOI: 10.1038/s41439-018-0016-8
|View full text |Cite|
|
Sign up to set email alerts
|

Novel variants in COL4A4 and COL4A5 are rare causes of FSGS in two unrelated families

Abstract: We report two female patients with focal segmental glomerulosclerosis and chronic kidney disease. The first patient was found to have a heterozygous, de novo, pathogenic variant in COL4A5 (c.141+1G>A, IVS2+1G>A), which is associated with Alport syndrome. The second patient was found to have a heterozygous, likely pathogenic variant in COL4A4 (c.2842G>T). Both these variants in COL4A5 and COL4A4 are novel, and they were detected using whole exome sequencing and gene panel testing, respectively. Additionally, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…However, no hearing impairments or symptoms in eyes were found in the proband. Older than 55 years old, the proband’s father only had asymptomatic microscopic hematuria and proteinuria, which was consistent with other reports[ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, no hearing impairments or symptoms in eyes were found in the proband. Older than 55 years old, the proband’s father only had asymptomatic microscopic hematuria and proteinuria, which was consistent with other reports[ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the formation of α3/4/5 chains and the abnormality of the basement membrane in our patient were the outcomes of the simultaneous action of these two mutations but could not be attributed solely to the missense mutation or the deletion; it was a complex heterozygous mutation, and the associated symptom was more severe than that with the simple missense mutation or with the single-base deletion mutation. Previous studies have focused on the relationship between FSGS and AS and on that between IgA nephropathy and AS (Gast et al, 2016;Hines et al, 2018;Kamiyoshi et al, 2016;Lin et al, 2014;Malone et al, 2014;Xie et al, 2015), suggesting that AS has variable clinical phenotypes, AS patients who have proteinuria or AS patients who have proteinuria and whose renal biopsy results are consistent with changes in FSGS or in IgA nephropathy are sometimes misdiagnosed with a primary nephropathy such as FSGS. In recent years, several…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the relationship between FSGS and AS and on that between IgA nephropathy and AS (Gast et al, ; Hines et al, ; Kamiyoshi et al, ; Lin et al, ; Malone et al, ; Xie et al, ), suggesting that AS has variable clinical phenotypes, AS patients who have proteinuria or AS patients who have proteinuria and whose renal biopsy results are consistent with changes in FSGS or in IgA nephropathy are sometimes misdiagnosed with a primary nephropathy such as FSGS. In recent years, several researches and cases reported that AS patients with COL4A5 mutations who have coinherited with COL4A3/COL4A4, MYO1E and LAMA5 mutations could exacerbated phenotypes (Lennon et al, ; Voskarides et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Both had histology consistent with TBMN. Though this gene has typically been associated with recessive Alport syndrome, multiple reports (Marcocci et al 2009;Hines et al 2018;Longo et al 2002) have demonstrated that patients with heterozygous COL4A4 or COL4A3 variants can develop significant renal disease and can benefit from early initiation of renin-angiotensinaldosterone system blockade (Stock et al 2017).…”
Section: Discussionmentioning
confidence: 99%